Atopic dermatitis - itchy problem of children and adults - Lasota, Nina; Demidowicz, Gabriela; Trąbka, Natalia; Lasek, Patryk; Smerdzyński, Maciej; Łach, Katarzyna; Ściurka, Kinga; Kowalczyk, Klaudia; Panuciak, Kinga; Kozicka, Karolina (Journal of Education, Health and Sport, 2024)
Atopic dermatitis is a chronic inflammatory disease with recurrent exacerbations, persistent itching, erythema, dry skin due to damage to the epidermal barrier, and staphylococcal infections. The causative factors are mutations in the gene encoding filaggrin, dysregulation of the immune system, changes in the skin microbiome and lipids in the stratum corneum and deficiency of antimicrobial peptides AMPs. The disease mainly affects children, causing a significant deterioration in the quality of life, and its first symptoms occur in approximately 90% before the age of 5. Lesions most often appear on the bends of elbows and knees, on the face and neck, but may also affect the skin of the entire body (erythroderma). The location of the eruptions depends on age. Atopic dermatitis is the result of complex genetic, epigenetic, environmental and immunological interactions with a coexisting epidermal barrier defect. The disease is diagnosed based on the Hanifin and Rajka criteria. Treatment of atopic dermatitis is symptomatic and selected individually. They include the elimination of provoking factors, care of the epidermal barrier, and anti-inflammatory and anti-pruritic therapy.